2016
DOI: 10.1007/s12298-016-0366-y
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in harvest index and bacoside A contents amongst accessions of Bacopa monnieri (L.) Wettst. collected from wild populations

Abstract: Bacoside A, a major active principle of Bacopa monnieri known for its cognitive effects is a mixture of saponins like bacoside A3, bacopaside II, isomer of bacopasaponin C and bacopasaponin C. Seasonal changes in biomass and bacoside A levels in fourteen accessions of B. monnieri were evaluated after maintaining these at a common site at Thapar University campus, Patiala (30°19 0 36.12 00 N and 76°24 0 1.08 00 E) for 1 year. Harvestable biomass and total bacoside A contents varied significantly between the acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…Bacoside content was quantified using the modified method of Bansal et al (2016). Briefly, aerial parts of 30-day-old hydroponically grown plants were dried at 40 °C for 2 days and then ground to a fine powder.…”
Section: Methodsmentioning
confidence: 99%
“…Bacoside content was quantified using the modified method of Bansal et al (2016). Briefly, aerial parts of 30-day-old hydroponically grown plants were dried at 40 °C for 2 days and then ground to a fine powder.…”
Section: Methodsmentioning
confidence: 99%
“…Seasonal variation i.e., the influence of temperature on wild varieties of B. monnieri plant on bacoside production was estimated by collect-ed samples from different regions (in India) and growing them in a uniform environment for one year. It was found that even though there were variations due to genotypic differences, the greatest amount of bacoside-A content (6.82 mg/plant) was documented during the summer, when the mean temperatures reached 40.0 o C and the lowest values (0.34 mg/ plant) during winter which recorded a mean temperature lower than 5.0 o C (Bansal et al 2016).…”
Section: Effect Of Abiotic Stress On B Monnierimentioning
confidence: 92%
“…Seasonal variations in harvest index and total bacoside contents were observed in wild populations of Bacopa monnieri. Principal component analysis showed that samples of summer were positively correlated with both the harvest index and total bacoside content thus suggesting an appropriate time for the harvest 78 . The efficient multiple shoots regeneration system developed may help in mass production of this most valuable plant and it will help to explore a suitable culture condition for large scale propagation for improving the production of commercially and therapeutically important bacosides all-round the year irrespective of season.…”
Section: Anti-bacterial Activitymentioning
confidence: 95%